THE STUDENTS’ MOTIVATION IN LEARNING ENGLISH AT SMP 1 CAMPALAGIAN - Asmawati, Andi; Mardiana; D., Ahmad Nur Safaat (elstic : english language linguistics culture, 2023)
This research intended to assess the English-learning motivation of SMP 1 Campalagian, Polman students. This research collected data on 131 individuals out of a total population of 196 students using the Slovin approach and proportionate random sampling. To meet the study aims, the researcher used a quantitative technique with a survey design. The instrument presented to students was a questionnaire designed to measure their motivation to study English. With an average score of 77, students in class VIII of SMP 1 Campalagian demonstrated a strong degree of desire to study English. Student motivation at SMP 1 Campalagian has a high level, and instrumental motivation is higher than integrative motivation with an instrumental motivation score of 39 and integrative motivation 38. The researcher drew the conclusion that the alternative hypothesis was supported by the data and that the null hypothesis was not. This meant that the desire to study English in SMP 1 Campalagian was high, particularly in class eight. The researcher advised the teachers that in order to achieve the intended learning outcomes, instrumental and integrative motivation play a crucial part in the process of learning English student.